Enhancement of Rydberg-mediated single-photon nonlinearities by electrically tuned Förster resonances - Gorniaczyk, H.; Tresp, C.; Bienias, P.; Paris-Mandoki, A.; Li, Weibin; Mirgorodskiy, I.; Büchler, H. P.; Lesanovsky, Igor; Hofferberth, S. (Nature Publishing Group, 2016)
We demonstrate experimentally that Stark-tuned Förster resonances can be used to substantially increase the interaction between individual photons mediated by Rydberg interaction inside an optical medium. This technique is employed to boost the gain of a Rydberg-mediated single-photon transistor and to enhance the non-destructive detection of single Rydberg atoms. Furthermore, our all-optical detection scheme enables high-resolution spectroscopy of two-state Förster resonances, revealing the fine structure splitting of high-n Rydberg states and the non-degeneracy of Rydberg Zeeman substates in finite fields. We show that the ∣50S1/2,48S1/2⟩↔∣49P1/2,48P1/2⟩ pair state resonance in 87Rb enables simultaneously a transistor gain G>100 and all-optical detection fidelity of single Rydberg atoms F>0.8. We demonstrate for the first time the coherent operation of the Rydberg transistor with G>2 by reading out the gate photon after scattering source photons. Comparison of the observed readout efficiency to a theoretical model for the projection of the stored spin wave yields excellent agreement and thus successfully identifies the main decoherence mechanism of the Rydberg transistor.